Cytotoxic cassane diterpenoids from the seeds of Caesalpinia sappan. - Wu, Z. F.; Bao, H.; Zhou, F. Y.; Liu, J. X.; Meng, F. C.; Feng, L.; Lin, L. G.
Phytochemical investigation on the seeds of Caesalpinia sappan led to the isolation of five new cassane-type diterpenoids, named 11-oxo-phanginin A (1), caesalsappanins O-Q (2-4)and phanginin U (5), together with five known compounds. The structures of the new compounds were elucidated by extensive analysis of mass spectrometric and 1D and 2D NMR spectroscopic data. All the new compounds showed moderate cytotoxic effects on human breast cancer MCF-7 and human colon cancer HCT116 cell lines.
Keywords: CAESALPINIA SAPPAN; CASSANE DITERPENOID; PHANGININ; CAESALSAPPANIN; CYTOTOXICITY